2016
DOI: 10.2174/1871527314666150821111812
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of the securinine-analogues: identification of Allomargaritarine as a lead compound

Abstract: Oxidative stress and mitochondrial disturbances are the common and important causative factors of aging, and play an important role in the late onset of sporadic neurodegenerative diseases, including Alzheimer disease (AD). Furthermore, emerging evidence from in vitro and in vivo disease models suggests that oxidative stress and increased vulnerability to induction of mitochondrial permeability transition leads to the pathogenesis of the neurological disorders. Towards the goals of developing effective neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…Алломаргаритарин проявляет выраженные нейропротекторные свойства, защищая нейроны первичной культуры коры мозга от гибели, вызванной эксайтотоксичностью, окислительным стрессом и Аb. Очевидно, этот эффект связан с его антиоксидантной и митопротекторной активностью [54,55]. Кроме того, алломаргаритарин снижает агрегацию Аb [56].…”
Section: ингибиторы мрт как перспективная группа лекарственных препарunclassified
“…Алломаргаритарин проявляет выраженные нейропротекторные свойства, защищая нейроны первичной культуры коры мозга от гибели, вызванной эксайтотоксичностью, окислительным стрессом и Аb. Очевидно, этот эффект связан с его антиоксидантной и митопротекторной активностью [54,55]. Кроме того, алломаргаритарин снижает агрегацию Аb [56].…”
Section: ингибиторы мрт как перспективная группа лекарственных препарunclassified
“…A study of the neuroprotective properties of this conjugate in various neurotoxicity models using a primary culture of the rat cortex showed that allomargaritarine has a pronounced cytoprotective effect that contributes to an increased cell survival rate after glutamate, Fe3+ and Aβ exposure. The ability of allomargaritarine to protect neurons from death correlated with its antioxidant potential: namely, there was a concentration-depended inhibition of lipid peroxidation caused by ferric iron ions and tert-butylhydroxyperoxide [ 41 , 42 ]. Allomargaritarine also has an anticonvulsant activity [ 43 ], which may be due to its antioxidant potential, since oxidative stress is known to be involved in the pathogenesis of epilepsy [ 44 , 45 ].…”
Section: Problems and Targets In The Treatment Of Neurodegeneative DImentioning
confidence: 99%
“…Preincubation of rat mitochondria with allomargaritarine, the conjugate of securinine and tryptamine, inhibits Ca 2+ -induced mitochondrial permeability transition in a dose-dependent manner. It also effectively suppresses it when Aβ35-25 is used as an inducer and, as a result, displays cyto(neuro)protector activity in models of excitotoxicity and toxicity mediated by trivalent iron ions and amyloid [ 41 , 42 , 168 ]. Moreover, allomargaritarine has the ability to reduce Aβ [ 169 ].…”
Section: Problems and Targets In The Treatment Of Neurodegeneative DImentioning
confidence: 99%
“…Процесс "набухания" митохондрий регистрировали спектрофотометрически в 96-луночных планшетах с прозрачным дном при 540 нм на планшетном анализаторе Victor 3 . В качестве индуктора "набухания" (скачка митохондриальной проницаемости) митохондрий использовали СаCl 2 [10]. Скорость "набухания" определяли в программе Excel как dA540/dt.…”
Section: исследование влияния соединений на митохондриальные характерunclassified